Changes to Yucatán Peninsula precipitation associated with salinity and temperature extremes of the Caribbean Sea during the Maya civilization collapse. Issue 1 (December 2017) - Wu, Henry; Felis, Thomas; Scholz, Denis; Giry, Cyril; Kölling, Martin; Jochum, Klaus; Scheffers, Sander
Abstract Explanations of the Classic Maya civilization demise on the Yucatán Peninsula during the Terminal Classic Period (TCP; ~CE 750–1050) are controversial. Multiyear droughts are one likely cause, but the role of the Caribbean Sea, the dominant moisture source for Mesoamerica, remains largely unknown. Here we present bimonthly-resolved snapshots of reconstructed sea surface temperature (SST) and salinity (SSS) variability in the southern Caribbean from precisely dated fossil corals. The results indicate pronounced interannual to decadal SST and SSS variability during the TCP, which may be temporally coherent to precipitation anomalies on the Yucatán. Our results are best explained by changed Caribbean SST gradients affecting the Caribbean low-level atmospheric jet with consequences for Mesoamerican precipitation, which are possibly linked to changes in Atlantic Meridional Overturning Circulation strength. Our findings provide a new perspective on the anomalous hydrological changes during the TCP that complement the oft-suggested southward displacement of the Intertropical Convergence Zone. We advocate for a strong role of Caribbean SST and SSS condition changes and related ocean-atmosphere interactions that notably influenced the propagation and transport of precipitation to the Yucatán Peninsula during the TCP.